Community-based infant hearing screening: Outcomes of a rural pilot programme - Khomotjo S. Kgare; Karin Joubert (South African Journal of Communication Disorders)
Background: Community-based universal newborn hearing screening (UNHS) has not been fully realised in South Africa despite the availability of contextually relevant early hearing detection and intervention guidelines. Research has confirmed the feasibility of implementing UNHS programmes in urban contexts; however, limited information exists for rural contexts.